Pemberdayaan Ibu Rumah Tangga dalam Meningkatkan Literasi Keuangan Rumah Tangga Desa Bajo Kecamatan Tilamuta - Sukrianto Sukrianto; Fibriyanti S. Lakoro; Syamsinah Syamsinah; Elan Rauf; Yuspita Hasan (Yayasan Literasi Sains Indonesia, 2025)
This Community Service activity aims to improve household financial literacy among housewives who are members of the Family Welfare Movement Team in Bajo Village, Tilamuta District, Boalemo Regency. The main problems faced by the partners include low levels of knowledge and skills in household financial management, weak financial planning and record-keeping, and the absence of a sustainable saving culture. The activity was implemented using a Participatory Action Research (PAR) approach through five stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability. The results show a 70% increase in financial literacy understanding, accompanied by changes in economic behavior from consumptive to more productive patterns, improved abilities in household financial planning and record-keeping, and the utilization of digital technologies such as the Money Lover application, Canva, and a household financial literacy website. In addition, a housewives’ financial literacy community was established to ensure program sustainability and to promote the strengthening of the local economy based on financial literacy and digital transformation. This model has the potential to be replicated in other villages as a form of women’s empowerment to enhance household economic resilience at the village level.